The three-point crossover technique for immediate reconstruction of the umbilicus - Cho Long Lee; Ho Jik Yang (Archives of Plastic Surgery, 2021)
The umbilicus is an important aesthetic component of the abdomen; therefore, its absence is both cosmetically and psychologically distressing to the patient. However, loss of the umbilicus during abdominal surgical procedures is often unavoidable. Umbilical reconstruction is aimed at obtaining a natural, three-dimensional appearance. We propose a simple method for immediate umbilical reconstruction with good long-term results. This technique was used successfully on a patient who underwent tumor excision. A 49-year-old woman presented with a large mass, measuring 5.8×4.0 cm, on her umbilicus. The mass, an epidermal cyst, developed after laparoscopic uterine myomectomy 5 years earlier. Complete excision of the mass resulted in a large defect, and immediate umbilical reconstruction was planned. Our procedure involved apposing and anchoring two opposing flaps onto the abdominal wall, so that the umbilicus would retain its depth over a long period of time. Negative-pressure wound therapy was applied for 72 hours as a mild compressive dressing. No complications were encountered. The healing process was uneventful and the aesthetic outcome was pleasing; a natural-appearing navel was created. The patient was satisfied with the end result. This technique provides a permanent and sufficient depression for the umbilicus.